Les Élections à l’Assemblée nord-irlandaise de 2016 et 2017 : contextes, résultats, perspectives - Karine Bigand (Revue Française de Civilisation Britannique)
The 2016 elections to the Northern Irish Assembly were the fifth since its creation in 1998 as part of the Belfast Agreement. As we know, the implementation of devolved institutions in Northern Ireland has not been plain sailing, and both the Assembly and the Executive were suspended several times. Although they have worked without official interruption since 2007, one cannot but observe that nearly 20 years into the post-conflict era, the internal structures of the institutions, as well as the quintessentially divided Northern Irish political landscape are detrimental to fluid and efficient debates and to the decision-making process – as is illustrated by the snap election called in March 2017, in a context of crisis and hostility between the two main parties. Both elections offer an opportunity to assess how far the road to normalisation has been travelled and remains to be travelled. Whereas words like stalemate and logjam are commonly and pointedly used to describe the work done on Stormont Hill, this article will show how the 2016 and 2017 elections have witnessed emerging new trends which might, possibly in the medium-term, kickstart a seemingly static system.